Epidemiologia comparativa da resinose (Lasiodiplodia theobromae) do cajueiro em pomares comerciais o semi-árido nordestino - Cysne, Alex Queiroz (2009)
Presently, a cashew disease known as gummosis, caused by the fungus Lasiodiplodia theobromae, deserves special attention due to its infection to branches and trunks of woody plants imposing significantly reduction in nut yield. As the importance of disease increases, it becomes of fundamental importance the development of epidemiological studies to understand the ecological aspects involved on disease establishment and progress. This work aimed to study gummosis dynamics in time and space in three different clones of cashew. Patterns of dispersion in space and disease progress on time, as well as the components involved on these models such as disease progress curve, maximum disease intensity, area under the disease progress curve and the point of initial disease were studied analyzed in order to compare epidemics in the three clones with different disease reactions. The study was conducted in a commercial cashew farm in Pio IX district in Piaui state, Brazil. Gummosis incidence and severity data of collected from 2002 to 2007 were used for both time and space analyses for BRS 226, Embrapa 51 and Faga 11 clones. Disregarding differences in disease occurrence and severity among clones, a random pattern of dispersion was observed at the beginning of the epidemic followed by the development of new foci and expansion of original foci. Later, a clustered pattern was observed. Clones showed different fitness to epidemic models accordingly with their degree of susceptibility. Comparison of epidemics based on their components have shown significant differences among clones, providing evidence for the potential use of host resistance as a means of gummosis control.